Socio-Religious Development for Muslims with Visually Impaired or Blind Disabilities in Manado City - Rajafi, Ahmad; Jan, Radlyah Hasan; Susanti, Ressi; Igisani, Rithon (Amalee: Indonesian Journal of Community Research and Engagement, 2022)
The purpose of community service by mentoring and coaching in socio-religious contexts for Muslims with visually impaired or blind disabilities in Manado city is to increase the spirit of religiosity and social lives. This community service activity was held at the Indonesian Muslim Disabilities Visibility Association office in Manado city from June to December 2021, employing the Asset Based Community Development method, prioritizing the utilization of existing assets and potential owned by them. As a result, there is an increase in knowledge in prayer practice. They can now implement fiqh thaharah and Janazah prayer practices well and perfectly. They also now can socialize by benefiting others, especially their readiness to be hosts or MCs, readers of the Qur'an, and preachers, beyond the skills they already have had. There were also jointly formulated by the program organizers and participants three follow-up solutions: continuous mental strengthening, a rapid environment learning, and constantly improving the special skills they have learned. Tujuan pengabdian kepada masyarakat dengan pendampingan dan pembinaan dalam konteks sosial keagamaan bagi tunanetra Muslim di kota Manado adalah untuk meningkatkan semangat keagamaan dan kehidupan sosial mereka. Kegiatan pengabdian masyarakat ini dilaksanakan di kantor Ikatan Tunanetra Muslim Indonesia di kota Manado pada bulan Juni hingga Desember 2021 dengan metode Asset Based Community Development yang mengutamakan pemanfaatan aset yang ada dan potensi yang telah dimiliki. Alhasil, terjadi peningkatan pengetahuan dalam amalan shalat. Mereka kini dapat melaksanakan amalan fiqh thaharah dan shalat Janazah dengan baik dan sempurna. Mereka juga kini bisa bersosialisasi dengan memberi manfaat bagi orang lain, terutama kesiapan mereka menjadi pembawa acara atau MC, pembaca Al-Qur'an, dan khatib, di luar keterampilan yang sudah mereka miliki sebelumnya. Ada pula tiga solusi tindak lanjut yang dirumuskan bersama oleh penyelenggara program dan peserta: penguatan mental terus-menerus, pembelajaran lingkungan yang cepat, dan terus-menerus meningkatkan keterampilan khusus yang telah mereka pelajari.